The Study of Teacher Role in Writing 3 Class at the English Department of Petra Christian University - Carmelia Lay (Institute of Research and Community Outreach - Petra Christian University, 2019)
In this study, the writer discussed types of teacher role in Writing 3 class at English Department of Petra Christian University. The purpose of this study was to find out the types of teacher roles and different treatments between regular and repeater students. The subject of this study was a lecturer teaching Writing 3 class at English Department of Petra Christian University. The theories used by the writer were types of teacher roles in writing class by Harmer (2007) and Richards (2015). The writer used classroom observation and video recording to collect the data. The findings of this study revealed that there were eight types of teacher role out of nine seen in Writing 3 class which were resource/facilitator, feedback provider/evaluator, motivator, expert writer, cultural informant, collaborator, investigator, and problem solver. As for the treatment, there were different treatments between regular and repeater students. From this study, it could be concluded that the teacher played eight roles out of nine types of teacher roles based on what the students needed and the teacher gave more attention to the repeater students. Key words: Teacher roles, repeater students, regular students, treatment